Vzgoja za trajnostni razvoj v praksi vrtcev - Lepičnik-Vodopivec, Jurka (Revija za elementarno izobraževanje, 2011)
Today we encounter sustainable development in all spheres of our lives. The first part of the paper discusses the purpose and the fundamental goals of education for sustainable development, which have been defined by the competent international organizations and adopted by the relevant national institutions in our country. The second part presents the opinions of teachers regarding the implementation of education for sustainable development in kindergartens, and its integration in kindergarten practice. The acquired empirical findings show that most teachers do implement education for sustainable development in the kindergarten they work at, and it is in fact integrated into kindergarten practice.
Keywords: education; predšolska vzgoja; predšolski otroci; sustainable development; trajnostni razvoj; kindergartens; otroški vrtci; kindergarten teachers; vzgojitelji